2015
DOI: 10.1155/2015/389531
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Reorganization Is Associated with Surgical Decompression of Cervical Spondylotic Myelopathy

Abstract: Background. Cervical spondylotic myelopathy (CSM) results in sensorimotor limb deficits, bladder, and bowel dysfunction, but mechanisms underlying motor plasticity changes before and after surgery are unclear. Methods. We studied 24 patients who underwent decompression surgery and 15 healthy controls. Patients with mixed upper and lower limb dysfunction (Group A) and only lower limb dysfunction (Group B) were then analysed separately. Results. The sum amplitude of motor evoked potentials sMEP (p < 0.01) and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Finally, 11 articles were included in this review and 21 were excluded because they did not meet the inclusion criteria (Figure ). The excluded articles are shown in Table …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 11 articles were included in this review and 21 were excluded because they did not meet the inclusion criteria (Figure ). The excluded articles are shown in Table …”
Section: Resultsmentioning
confidence: 99%
“…Green et al 19 performed TMS and motor function testing 1 month prior to and 4 months after surgery for CSM. They showed that the sum amplitude of motor evoked potentials (sMEPs) and number of focal points at which MEPs were elicited (N) were significantly greater in CSM patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…35 Not many studies have correlated the postoperative motor improvement with plasticity. 19 Some studies have shown adaptive changes in bilateral primary motor cortex (M1), supplementary motor area (SMA), premotor area (PMA), cingulate motor area, parietal cortex, and contralateral primary somatosensory cortex (S1) in cases of SCI [8][9][10][11][27][28][29]33,40 and cervical compressive myelopathy due to spondylosis. 13,14,23,38 In this study we aimed to understand the cortical changes that occur due to CSM and following CSM surgery and to correlate these changes with functional recovery by using functional MRI (fMRI).…”
mentioning
confidence: 99%
“…It is also known that the intraoperative MEPI alone might not be adequate for predicting postoperative results. Several studies, 22 including ours, 5 have shown that cortical reorganization over 6 months and beyond may contribute to functional improvement during the postoperative recovery phase, possibly even up to 2 years later. 23 Improvement in upper limb dexterity has also been shown to be related to recruitment in motor areas including the postcentral gyrus, precentral gyrus, and premotor and supplementary motor areas 24 over a 6-month postoperative period and beyond.…”
Section: Jcnmentioning
confidence: 71%
“…1,2 There is evidence from previous studies that the improvement of motor function after surgical decompression in CSM patients occurs via synaptic changes and dendritic sprouting in the cortical and spinal cord neuron pools. [3][4][5] In CSM, compression of descending corticospinal tracts results in desynchronization of I-wave volleys evoked by single-pulse transcranial magnetic stimulation (TMS) of the primary motor cortex. A prospective study of 141 CSM patients demonstrated a strong correlation of MRI findings with central motor conduction times in terms of sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%